Selection of endogenous control and identification of significant microRNA deregulations in cervical cancer - Stverakova, T.; Baranova, I.; Mikyskova, P.; Gajdosova, B.; Vosmikova, H.; Laco, J.; Palicka, V.; Parova, H. (Frontiers in Oncology, 2023)
Introduction Cervical cancer causes approximately 350,000 deaths each year. The availability of sensitive and specific diagnostic tests to detect cervical cancer in its early stages is essential to improve survival rates. Methods In this study, we compared two strategies for selecting endogenous controls: miRNA profiling by small-RNA sequencing and a commercially available microfluidic card with 30 recommended endogenous controls preloaded by the manufacturer. We used the RefFinder algorithm and coefficient of variation to select endogenous controls. We selected the combination of miR-181a-5p and miR-423-3p as the most optimal normalizer. In the second part of this study, we determined the differential expression (between tumor/non-tumor groups) of microRNA in cervical cancer FFPE tissue samples. We determined the comprehensive miRNA expression profile using small-RNA sequencing technology and verified the results by real-time PCR. We determined the relative expression of selected miRNAs using the 2-ΔΔCt method. Results We detected statistically significant upregulation of miR-320a-3p, miR-7704, and downregulation of miR-26a-5p in the tumor group compared to the control group. The combination of these miRNAs may have the potential to be utilized as a diagnostic panel for cervical cancer. Using ROC curve analysis, the proposed panel showed 93.33% specificity and 96.97% sensitivity with AUC = 0.985. Conclusions We proposed a combination of miR-181a-5p and miR-423-3p as optimal endogenous control and detected potentially significant miRNAs (miR-320a-3p, miR-7704, miR-26a-5p). After further validation of our results, these miRNAs could be used in a diagnostic panel for cervical cancer.